2012
DOI: 10.1103/physrevb.85.201105
|View full text |Cite
|
Sign up to set email alerts
|

Fate of topological-insulator surface states under strong disorder

Abstract: Three-dimensional topological insulators feature Dirac-like surface states which are topologically protected against the influence of weak quenched disorder. Here we investigate the effect of surface disorder beyond the weak-disorder limit using large-scale numerical simulations. We find two qualitatively distinct regimes: Moderate disorder destroys the Dirac cone and induces diffusive metallic behavior at the surface. Even more remarkably, for strong surface disorder a Dirac cone reappears, as new weakly diso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 28 publications
6
99
5
Order By: Relevance
“…Indeed, surface states or edge states are shown to persist in the presence of weak disorders [5]. However, it is also found that in the presence of disorders, anomalous transmutation between TI and insulators with trivial topology may happen [9,10,12]. In particular, in computer simulations of a HgTe quantum well, it is discovered that an ordinary insulating state can be transformed into a topological insulator, called topological Anderson insulator [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, surface states or edge states are shown to persist in the presence of weak disorders [5]. However, it is also found that in the presence of disorders, anomalous transmutation between TI and insulators with trivial topology may happen [9,10,12]. In particular, in computer simulations of a HgTe quantum well, it is discovered that an ordinary insulating state can be transformed into a topological insulator, called topological Anderson insulator [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Since topological order is protected by associated symmetries [4], surface states and edge states in TIs are considered to be robust against bulk disorders that do not break the time-reversal symmetry that is associated with Z 2 topological order. The robustness against disorders is the key to potential technological applications and hence a great effort has been dedicated to understanding the behavior of the topological materials in the presence of disorders [5][6][7][8][9][10]12]. Indeed, surface states or edge states are shown to persist in the presence of weak disorders [5].…”
Section: Introductionmentioning
confidence: 99%
“…Kondo holes on the surface of TKIs promise to be interesting also because they represent strong scatterers for which the simplest arguments of topological protection no longer apply. 29,30 Here we will employ a fully self-consistent mean-field description of the Kondo insulator, taking into account the local modification of Kondo screening by defects. Applying this methodology to both the weak topological insulator (WTI) and strong topological insulator (STI) phases, we will calculate the electronic structure and the surface QPI patterns for dilute surface Kondo holes as well as for other types of impurities.…”
Section: -18mentioning
confidence: 99%
“…5) on the surface of as-grown topological insulator Bi 2−x Cu x Se 3 which is necessary to prevent the surface band bending caused by the adsorption of residual atoms present in the vacuum chamber. As the manifestations of topological systems -such as the protected surface states or Majorana fermions -are localized near the surface or the edge of the system [11][12][13][14][15] , the effect of surface impurities on the surface spectral and transport properties are of both theoretical and practical interest [16][17][18] . Impurity effects could be apparent through the Local density of states (LDOS), and spectral functions.…”
Section: Introductionmentioning
confidence: 99%
“…The only general analysis of surface impurities was given recently, when an exact diagonalization (ED) approach has been applied to non-interacting TIs with surface disorder 16,19 (recent additional work was dedicated to surface Kondo effects in 3D TI's 20,21 ). This study found evidence for a crossover between a nearly ballistic response of the surface electrons at weak disorder, localization physics at intermediate disorder, and then a restored nearly ballistic surface state hiding in the second layer when disorder is very strong.…”
Section: Introductionmentioning
confidence: 99%